Răspuns :
b) 4x² + 12x + 9 - 4(x² + 2x + x + 2) =
4x² + 12x + 9 - 4x² - 8x - 4x - 8 = 1
d) x² - 3x + 3x + 9 - (x²+ 4x + 4) =
x² + 9 - x² - 4x - 4 = - 4x + 5
4x² + 12x + 9 - 4x² - 8x - 4x - 8 = 1
d) x² - 3x + 3x + 9 - (x²+ 4x + 4) =
x² + 9 - x² - 4x - 4 = - 4x + 5
B) (2x) la 2 + 12x + 9 - 4(x la 2 +2x+x+2 ) = 2x la 2 +12x + 9 - 4x la 2 -8x-4x-8 = - 2x la 2 + 1
D) x la 2 - 9 - ( x la 2 + 4x + 4 ) = x la 2 - 9 -x la 2-4x-4 = -4x - 13
D) x la 2 - 9 - ( x la 2 + 4x + 4 ) = x la 2 - 9 -x la 2-4x-4 = -4x - 13